Clusters of floor locations-allocation of stores to cross-docking warehouse considering satisfaction and space using MOGWO and NSGA-II algorithms - Shoaee, Maryam; Samouei, Parvaneh (Flexible services and manufacturing journal, 2024)
Optimal warehouse design is the most substantial issue for many companies, because of increasing their efficiency and productivity. Nowadays, a warehouse is just undefined as a site for goods storage and delivery but is taken into account as a unit interacting with other sectors. Recently, cross-docking warehouses have been widely used since they differ from traditional warehouses in terms of good deposition volume, storage and delivery times, mitigating procurement, exploitation of resources, and accelerating service pace. This study proposes a mathematical model for transit warehouse layout and design to minimize travel distances, downsize the free space of the warehouse and make retailers satisfied. Small-sized problems are solved by the augmented epsilon-constraint and the weighted sum methods, while NSGA-II and MOGWO algorithms are proposed for large-sized problems. Comparison between algorithms indicates higher efficiency of NSGA-II rather than MOGWO algorithm to solve cross-docking warehouse design for allocating stores to floor locations.